The Role of Competence and Intellect in Promoting Sports Tourism in Rivers State - Okala, Chikaike (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2025)
The study investigated the role of competence and intelligence in promoting sports tourism in Rivers State, Nigeria. A correlational survey design was adopted. A sample size of five hundred (500) workers from ministry of sports was gotten using the purposive sampling procedure. Two research questions and hypotheses guided the study. The instrument that was used for data collection was a validated questionnaire with a modified likert scale. The instrument's reliability coefficient of 0.80 was attained using Cronbach Alpha, which was deemed acceptable. The data collected was analysed using simple regression analysis, at the 0.05 level of significance. The results showed a strong positive correlation between sports tourism promotion and intellect (r = 0.792), sports tourism promotion and competence (r = 0.809). The findings of a simple regression analysis reveal that intelligence in sports contribute approximately 63% and competence contributes 65.4% to the promotion of sports tourism in Rivers State which has a significant impact on sports tourism development. Consequently, the study recommended amongst other that, professional development programs should be designed to focus on enhancing the identified personality traits, training initiatives that can help individuals in the sports tourism sector improve their decision-making, leadership, and collaboration skills.